Implementasi Sistem E-Voting Berbasis Blockchain Menggunakan Teknologi Internet Computer Protocol (ICP) - Aditya Premana Putra; Ngurah Agus Sanjaya ER; I Gusti Agung Gede Arya Kadyanan (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
This research develops and implements a blockchain e-voting system using the Internet Computer Protocol (ICP), addressing challenges in conventional voting such as data manipulation, security, and transparency. The study explores e-voting and blockchain technologies, particulary ICP, to enhance secure voting processes. The system lavarages blockchain’s decentralization, transparency, and immutability, ensuring transparent and permanent vote recording. Smartcontracts automate vote data recording and security within the blockchain. Initial testing demonstrates the system’s stability, effective voter authentication, and accurate vote data reporting.